2009
DOI: 10.1007/s00203-009-0491-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Bifidobacterium animalis, Escherichia coli, Lactobacillus casei and Saccharomyces boulardii probiotic properties

Abstract: The present work investigates some probiotic properties of four different microorganisms (Bifidobacterium animalis var. lactis BB-12, Escherichia coli EMO, Lactobacillus casei and Saccharomyces boulardii). In vitro and in vivo tests were carried out to compare cell wall hydrophobicity, production of antagonistic substances, survival capacity in the gastrointestinal tract of germ-free mice without pathological consequence, and immune modulation by stimulation of Küpffer cells, intestinal sIgA and IL-10 levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 39 publications
2
44
1
8
Order By: Relevance
“…Then, they were centrifuged (2000 g, 30 min, 4 uC) and the supernatant collected and frozen at 280 uC for later determination of immunoglobulins. The determination of total sIgA levels was performed by ELISA as previously described by Martins et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…Then, they were centrifuged (2000 g, 30 min, 4 uC) and the supernatant collected and frozen at 280 uC for later determination of immunoglobulins. The determination of total sIgA levels was performed by ELISA as previously described by Martins et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that the administration of probiotic organisms can increase total secretory IgA levels in rodents (148,(152)(153)(154), which may contribute to the control of C. difficile bacteria (72,(77)(78)(79)(80)(81). S. boulardii, for example, increases total secretory IgA levels in conventional rats and mice as well as in germfree mice colonized with S. boulardii (148,(152)(153)(154)(155). Studies of Bifidobacterium animalis subsp.…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 99%
“…Studies of Bifidobacterium animalis subsp. lactis BB-12, Escherichia coli EMO, and Lactobacillus casei and L. rhamnosus strains showed effects on total secretory IgA levels in rodent models (153,(156)(157)(158). However, the mechanisms by which some probiotics increase secretory IgA levels are not well understood, and more studies are needed to determine whether such changes in antibody production could protect against CDI.…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 99%
“…Установлено, что данный пробиотический штамм: ■ способен к высокоуровневой адгезии к поверхностям с муцином, без муцина и пленкам клеточных культур [34]; ■ устойчив к действию агрессивных сред организма че-ловека -соляной кислоты и желчи, за счет синтеза рН-зависимой АТФ-азы, регулирующей кислотно-основ-ной баланс внутри бактерии и наличия гидролазы солей желчных кислот, позволяющей бактерии сохранять актив-ность в присутствии желчи [35] [36]; и резистентностью к таким антибиотикам, как гентамицин, стреп-томицин, полимиксин В, канамицин, нео мицин, циклосерин, тетрациклин и налидиксовая кислота [37] -способ-ствует улучшению барьерной функции кишечного эпителия (повышение кон-центрации секреторного IgA) [38,39] и положительно влияет на работу иммун-ной системы [40].…”
Section: пробиотики при коррекции функциональных нарушений органов пиunclassified